Validation of the United Kingdom copy-number alteration classifier in 3239 children with B-cell precursor ALL - Hamadeh, Lina; Enshaei, Amir; Schwab, Claire; Alonso, Cristina N; Attarbaschi, Andishe; Barbany, Gisela; den Boer, Monique L; Boer, Judith M; Braun, Marcin; Dalla Pozza, Luciano; Elitzur, Sarah; Emerenciano, Mariana; et al. (Blood advances, 2019)
Genetic abnormalities provide vital diagnostic and prognostic information in pediatric acute lymphoblastic leukemia (ALL) and are increasingly used to assign patients to risk groups. We recently proposed a novel classifier based on the copy-number alteration (CNA) profile of the 8 most commonly deleted genes in B-cell precursor ALL. This classifier defined 3 CNA subgroups in consecutive UK trials and was able to discriminate patients with intermediate-risk cytogenetics. In this study, we sought to validate the United Kingdom ALL (UKALL)-CNA classifier and reevaluate the interaction with cytogenetic risk groups using individual patient data from 3239 cases collected from 12 groups within the International BFM Study Group. The classifier was validated and defined 3 risk groups with distinct event-free survival (EFS) rates: good (88%), intermediate (76%), and poor (68%) (P < .001). There was no evidence of heterogeneity, even within trials that used minimal residual disease to guide therapy. By integrating CNA and cytogenetic data, we replicated our original key observation that patients with intermediate-risk cytogenetics can be stratified into 2 prognostic subgroups. Group A had an EFS rate of 86% (similar to patients with good-risk cytogenetics), while group B patients had a significantly inferior rate (73%, P < .001). Finally, we revised the overall genetic classification by defining 4 risk groups with distinct EFS rates: very good (91%), good (81%), intermediate (73%), and poor (54%), P < .001. In conclusion, the UKALL-CNA classifier is a robust prognostic tool that can be deployed in different trial settings and used to refine established cytogenetic risk groups.
Keywords: Young Adult; proporcionální rizikové modely; hodnocení výsledků pacienta; genetické asociační studie; Male; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Child, Preschool; Genetic Predisposition to Disease; DNA Copy Number Variations; pre-B-buněčná leukemie; mladý dospělý; Cytogenetic Analysis; United Kingdom; následné studie; Adolescent; Genetic Association Studies; prognóza; Infant; Child; Proportional Hazards Models; Population Surveillance; dítě; mužské pohlaví; variabilita počtu kopií segmentů DNA; mladiství; Follow-Up Studies; předškolní dítě; Patient Outcome Assessment; lidé; ženské pohlaví; Humans; kojenec; Spojené království; surveillance populace; Prognosis; Female; cytogenetické vyšetření; Biomarkers, Tumor; nádorové biomarkery; genetická predispozice k nemoci